Pengaruh Customer Relationship Management dan After Sales Services terhadap Peningkatan Penjualan Produk Elektronik : Studi Kasus PT. Xiaomi Technology Indonesia - Muhammad Yunus Sofian; Juliana Nasution; Budi Dharma (LPPM Institut Nasional Laa Roiba Bogor, 2024)
CRM and After sales services is a services provided by companies to build communication and service bridges between companies and consumers so that they are interested in buying products. The purpose of this study is to determine the business model and CRM relationship carried out by PT. Xiaomi Technology Indonesia and look at the after-sales service carried out by the company on the increase in sales of the electronic products it produces. This research was conducted using a Mixed Methods approach. This study uses primary data collected through interviews with the Xiaomi Official Store Center Point Mall Medan as well as distributing research instruments in the form of questionnaires to Xiaomi product users in Indonesia. The research data was tested and processed with the help of the SPSS version 24 application and analyzed using several tests such as the classical assumption test, as well as multiple linear analysis. The results of this study show that there is a significant influence between customer relationship management (CRM) and After Sales Services on increasing sales of Xiaomi Technology Indonesia's electronic products and the strategy implemented by Xiaomi Technology Indonesia has proven to be in line with expectations. Keywords: Customer, Customer Relationship Management, Product